Membandingkan Nilai Tukar Petani Padi Dan Palawija Di Sulawesi Utara - Hutabarat, Estheria; Katiandagho, Theodora Maulina; Laoh, Esry Olly Harryani (AGRI-SOSIOEKONOMI, 2024)
The purpose of this study was to compare farmers' exchange rate between rice and secondary crops in North Sulawesi Province. The research lasted for 3 months from September to November 2023, conducted at the BPS office of North Sulawesi Province. The data used in this research data is secondary data, namely data on the exchange rate of rice and food crop farmers obtained from other parties in the form of finished data in the form of publications in the form of monthly farmer exchange rate developments at the North Sulawesi Province level. The data used in this study is data in the form (time series) of the last 2 years from 2021 to 2022. The data was obtained from various sources, namely the Central Bureau of Statistics (BPS) and website sources related to the research. The variables measured in this study are the period in years of data on food crops, namely rice and secondary crops. Data analysis method of calculation formula of It and Ib, calculation of NTP, calculation of NTUP, T test analysis, and Trend analysis. The results showed that the farmer exchange rate on secondary crops was higher than the farmer exchange rate on rice, which meant that the purchasing power of farmers was higher.